A FLUID FLOW ANALYSIS OF A JET EJECTOR SYSTEM USED IN INDUSTRIAL APPLICATIONS - IONEL OLARU (Journal of Engineering Studies and Research)
Many studies have been conducted for jet ejectors used in the recovery of solar energy or for their use in refrigeration systems for various industrial applications. Generally, these types of ejectors are using water as the working fluid because water have a low cost, a chemical stability and is safe to use. Naturally, other refrigerants, with large-scale application for industry, can be used. In such a type of jet ejector, besides selection of the refrigerant, the design of ejector is very important, with strongly influence to the performance, because the compression ratio depends on the geometry of the nozzle and on the geometry of the diffuser. Compared to other refrigeration systems, those with ejector have some advantages: simplicity in construction, high liability and low cost. However, it has a coefficient of performance lower than conventional systems, this limited the widespread application of ejector refrigeration systems.